2022
DOI: 10.3389/fpsyg.2022.883150
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Mapping of Volunteer Motivation: A Bibliometric Analysis and Cross-Cultural Comparative Study

Abstract: Volunteers play an indispensable role in several major events and activities. The purpose of this study is to review studies on volunteer motivation from 2000 to 2021 and to discover the development trends in this field. The Web of Science Core Collection is the main literature data resource, from which 162 papers on volunteer motivation published in the SSCI were selected. Using two visualization analysis tools, CiteSpace and VOSviewer, this study conducts bibliometric analysis and systematic review from mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 135 publications
0
9
0
Order By: Relevance
“…This later point was buttressed by Afari-Asiedu et al [37] result where the volunteers deemed it as a pleasure to be chosen by community leaders and given the duty of assisting healthcare provision in the community. The feeling of achievement is an important factor in the promotion of volunteer work and, moreover, an important part of the motivation of volunteer works [17]. Meanwhile, many of the VHVs have low motivation about the believe that wearing a mask, washing of hands for at least 20 seconds, and maintaining a distance of 2 meters between people can prevent/reduce COVID-19 infection, and this may be due to the no or limited training received by this set of VHVs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This later point was buttressed by Afari-Asiedu et al [37] result where the volunteers deemed it as a pleasure to be chosen by community leaders and given the duty of assisting healthcare provision in the community. The feeling of achievement is an important factor in the promotion of volunteer work and, moreover, an important part of the motivation of volunteer works [17]. Meanwhile, many of the VHVs have low motivation about the believe that wearing a mask, washing of hands for at least 20 seconds, and maintaining a distance of 2 meters between people can prevent/reduce COVID-19 infection, and this may be due to the no or limited training received by this set of VHVs.…”
Section: Discussionmentioning
confidence: 99%
“…Health workers who provide treatment for COVID-19 patients have been reported to have greater rates of sadness, anxiety, sleeplessness, distress and mental pressure compared to other healthcare professionals, due to COVID-19's highly infectious nature and lack of specific vaccine for treatment [14,15,16]. Chen et al [17] also opined that doctors, nurses and other health workers are dealing with mental health issues due to this pandemic. With the above mentioned challenges, there is a need for the implementation of healthy behavioural theory among health workers to successfully prevent the spread of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the Eastern conceptualization of happiness aligns more with eudaimonic motive-based happiness [ 63 ]. The emphasis on the contribution to society or the community in Chinese culture was also supported by a bibliometric study of 162 publications from 2000 to 2021 comparing volunteer motivation between Chinese and American volunteers [ 64 ]. Therefore, future research should explore strategies to promote the eudaimonic motives of formal volunteers to achieve an optimal level of life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, results from a longitudinal study suggested that self-esteem tended to be an antecedent rather than a consequence of social support in adults [ 14 ]. Another study reported that self-esteem and behavioral activation, both independent and serially, mediated the positive association between cheerfulness and life satisfaction [ 64 ]. Hence, these studies suggested that individuals with higher levels of self-esteem tended to predict greater life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to ensure that the literature included in the analysis was closely related to the relevant topics, software was required to remove and manually screen the literature included in the analysis after the initial literature search. Doing so prevents the analytical results from suffering due to data quality problems (Chen et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%